Quantitative imaging of anti-phase domains by polarity sensitive orientation mapping using electron backscatter diffraction - Naresh-Kumar, G; Vilalta-Clemente, A; Jussila, H; Winkelmann, A; Nolze, G; Vespucci, S; Nagarajan, S; Wilkinson, A; Trager-Cowan, C (Springer Nature, 2017)
Advanced structural characterisation techniques which are rapid to use, non-destructive and structurally definitive on the nanoscale are in demand, especially for a detailed understanding of extended-defects and their influence on the properties of materials. We have applied the electron backscatter diffraction (EBSD) technique in a scanning electron microscope to non-destructively characterise and quantify antiphase domains (APDs) in GaP thin films grown on different (001) Si substrates with different offcuts. We were able to image and quantify APDs by relating the asymmetrical intensity distributions observed in the EBSD patterns acquired experimentally and comparing the same with the dynamical electron diffraction simulations. Additionally mean angular error maps were also plotted using automated cross-correlation based approaches to image APDs. Samples grown on substrates with a 4° offcut from the [110] do not show any APDs, whereas samples grown on the exactly oriented substrates contain APDs. The procedures described in our work can be adopted for characterising a wide range of other material systems possessing non-centrosymmetric point groups.